Impact of Ketogenic and Mediterranean Diets on Gut Microbiota Profile and Clinical Outcomes in Drug-Naïve Patients with Diabesity: A 12-Month Pilot Study - Vanessa Palmas; Andrea Deledda; Vitor Heidrich; Giuseppina Sanna; Giulia Cambarau; Michele Fosci; Lorenzo Puglia; Enrico Antonio Cappai; Alessio Lai; Andrea Loviselli; Aldo Manzin; Fernanda Velluzzi (Metabolites)
Background/Objectives: Managing type 2 diabetes mellitus (T2DM) and obesity requires a multidimensional, patient-centered approach including nutritional interventions (NIs) and physical activity. Changes in the gut microbiota (GM) have been linked to obesity and the metabolic alterations typical of T2DM and obesity, and they are strongly influenced by diet. However, few studies have evaluated the effects on the GM of a very-low-calorie ketogenic diet (VLCKD) in patients with T2DM, especially in the mid-term and long-term. This longitudinal study is aimed at evaluating the mid-term and long-term impact of the VLCKD and Mediterranean diet (MD) on the GM and on the anthropometric, metabolic, and lifestyle parameters of 11 patients with T2DM and obesity (diabesity). This study extends previously published results evaluating the short-term (three months) impact of these NIs on the same patients. Methods: At baseline, patients were randomly assigned to either a VLCKD (KETO group) or a Mediterranean diet (MEDI group). After two months, the KETO group gradually shifted to a Mediterranean diet (VLCKD-MD), according to current VLCKD guidelines. From the fourth month until the end of the study both groups followed a similar MD. Previous published results showed that VLCKD had a more beneficial impact than MD on several variables for 3 months of NI. In this study, the analyses were extended until six (T6) and twelve months (T12) of NI by comparing data prospectively and against baseline (T0). The GM analysis was performed through next-generation sequencing. Results: Improvements in anthropometric and metabolic parameters were more pronounced in the KETO group at T6, particularly for body mass index (−5.8 vs. −1.7 kg/m2; p = 0.006) and waist circumference (−15.9 vs. −5.2 cm; p = 0.011). At T6, a significant improvement in HbA1c (6.7% vs. 5.5% p = 0.02) and triglyceride (158 vs. 95 mg/dL p = 0.04) values compared to T0 was observed only in the KETO group, which maintained the results achieved at T3. The VLCKD-MD had a more beneficial impact than the MD on the GM phenotype. A substantial positive modulatory effect was observed especially up to the sixth month of the NI in KETO due to the progressive increase in bacterial markers of human health. After the sixth month, most markers of human health decreased, though they were still increased compared with baseline. Among them, the Verrucomicrobiota phylum was identified as the main biomarker in the KETO group, together with its members Verrucomicrobiae, Akkermansiaceae, Verrucomicrobiales, and Akkermansia at T6 compared with baseline. Conclusions: Both dietary approaches ameliorated health status, but VLCKD, in support of the MD, has shown greater improvements on anthropometric and metabolic parameters, as well as on GM profile, especially up to T6 of NI.